Model of Intention to Purchase Environmentally Friendly Products of SMEs Deli Serdang - Nel Arianty; Julita; Sri Fitri Wahyuni (Jurnal Manajemen, 2025)
This study aims to determine how the green marketing model is developed in small and medium enterprises to increase consumer buying interest during the new normal period in the Deli Serdang Regency. From the data processing results using Structural Equation Modeling (SEM) Partial Least Square (PLS). The study results indicate that green products to increase consumer buying interest are negative and insignificant. Green products cannot increase consumer buying interest. Green prices to increase consumer buying interest are negative and significant. Green prices can increase consumer buying interest. Green places to increase consumer buying interest are positive and insignificant. At the same time, green promotion towards consumer buying interest is positive and significant. When viewed from the data processing, SME business actors in Deli Serdang Regency need to develop a green marketing model.